The implications of derisking: The case of Malta, a small EU state - Simon Grima; Peter J. Baldacchino; Jeremy Mercieca Abela; Jonathan V. Spiteri (Journal of Risk and Financial Management, 2020)
In this study, we explore the emerging derisking phenomenon by identifying and analysing the main factors that are affected by, and the implications of, the derisking process by focusing on the key drivers and implications of derisking specific to Malta. To do this, we carried out 32 interviews with individuals who have a good or excellent level of expertise in derisking and administered a survey, completed by 296 participants who were filtered to ensure their level of expertise, resulting in 285 valid participant surveys. In total, between the interviews and the survey, we had 317 valid participants. Findings showed that to maximise the effectiveness of derisking, one needs to find the right balance of adequately managing risks without extinguishing business needs. This implies a need for the regulations to be balanced and proportionate. This study is a relevant contributor to future derisking to be conducted in Malta and serves as a benchmark for further studies. Moreover, this research project accentuates the need for increased awareness, knowledge and expertise of derisking in Malta. Consequently, the provision of education to professionals is important so that such professionals are able to keep abreast with all the latest developments regarding derisking and AML/CFT (antimoney laundering and combatting the financing of terrorism).
Keywords: 330; risk management; antimoney laundering (AML); combatting the financing of terrorism (CFT); derisking; drivers and implications of derisking; financial services; Malta; proportionality; small EU state